Implementation of the Advance Organizer Learning Model to Improve the Scientific Attitude of Class X Students Senior High School - Umi Kalsum; Azizahwati Azizahwati; Zulhelmi Zulhelmi (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2020)
This research aimed to describe the scientific attitudes of students towards learning physics on energy and work materials by applying the advanced organizer learning model. This research is pre-experimental research with the design of one group pretest-posttest design, which describes an increase in scientific attitudes through the application of the advance organizer learning model for Class X SMA 2 Mempura, Siak Regency in the 2018/2019 academic year. The aspects of the scientific attitude in this research include curiosity, critical thinking, open thinking, and honest attitude. The data collection technique used a questionnaire given to the research subject. Initial scientific attitude data was taken by distributing questionnaires to research subjects before treatment, while the final scientific attitude was taken by distributing questionnaires after treatment. The filling out of the questionnaire is done individually in the class, where students are not allowed to ask questions or pay attention to other friends regarding the answers to the questionnaire. The results showed that the students' initial scientific attitude was in the low category of 2.41, while the final scientific attitude had increased by 1.11 points with an average score of 3.52 which was categorized as high. Based on the results of the N-Gain score, students' scientific attitudes on each indicator had a score with an average N-Gain value of 0.70 which was categorized as high. The results of this research concluded that the application of the advanced organizer learning model in learning work and energy materials could improve the scientific attitudes of class X students SMA 2 Mempura.